2016
DOI: 10.1021/acs.jced.6b00333
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Hydrate Dissociation Conditions of CO2 + HCFC141b or Cyclopentane

Abstract: Equilibrium hydrate dissociation conditions (vapor + hydrate + liquid water + liquid HCFC141b or cyclopentane) formed from CO2 + water + HCFC141b or cyclopentane are determined using an isochoric method in this work. HCFC141b and cyclopentane are reported to form the structure II hydrates. Phase equilibrium pressures of the experimental systems of CO2 + water + HCFC141b or cyclopentane are all lower than that of CO2 + H2O at any given temperatures. The presence of HCFC141b has more effect on lowering CO2 hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…In this work, CO2 Kihara parameter have been taken from Herri et al (Herri et al, 2011). CP parameters have been obtained by mathematical regression upon data in pure water from Wang et al (Wang et al, 2016), data from NaCl solution from Zhang et al (Zhang et al, 2017) and our equilibrium measurements. The geochemical model PHREEQC has been employed to provide water activity in brine solutions.…”
Section: Modelling Thermodynamic Equilibrium Of Mixed Cp/co2 Hydratesmentioning
confidence: 99%
“…In this work, CO2 Kihara parameter have been taken from Herri et al (Herri et al, 2011). CP parameters have been obtained by mathematical regression upon data in pure water from Wang et al (Wang et al, 2016), data from NaCl solution from Zhang et al (Zhang et al, 2017) and our equilibrium measurements. The geochemical model PHREEQC has been employed to provide water activity in brine solutions.…”
Section: Modelling Thermodynamic Equilibrium Of Mixed Cp/co2 Hydratesmentioning
confidence: 99%
“…Wang et al examined the equilibrium hydrate dissociation conditions of CO 2 + 1,1-dichloro-1-fluoroethane (HCFC 141b)/cyclopentane (CP). They reported that the addition of HCFC 141b or CP reduced the CO 2 –hydrate equilibrium pressures …”
Section: Introductionmentioning
confidence: 99%
“…In the previous work, the pure CO 2 hydrate equilibrium dissociation data were measured using the same experimental apparatus and the same method to verify the effectiveness of the experimental method by Wang et al 27 and Dai et al 36 of our research group. As shown in Figure 2, the literature data 37 is consistent with the data measured by Wang et al 27 and Dai et al, 36 which shows that the experimental setup and method are validated.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 1 shows the experimental apparatus, which is the same as that used in previous works. 27,32,33 A high-pressure cell was used for hydrate formation in this work, which was manufactured by Haian Petroleum Instrument Co. Ltd. Its volume was about 500 cm 3 , and the working pressure can reach 20 MPa. The formation and dissociation processes of gas hydrate can be observed from the plexiglass windows on both sides of the cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation